PENGARUH KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT DI KANTOR DESA POTOKULLIN, KECAMTAN BUNTU BATU, KABUPATEN ENREKANG - Arnita, Reni; Sapri, Sapri; Ikbal, Muhammad (Universitas Gajah Putih, 2025)
Abstract. This study aims to determine the influence of employee performance on community satisfaction at the Potokullin Village Office, Buntu Batu District, Enrekang Regency. The research approach used is a descriptive quantitative method. The population in this study consisted of approximately 95 people from Potokullin Village. The sampling technique used was incidental sampling. Data collection techniques included observation, questionnaires, and literature studies. The collected data was then processed and analyzed using descriptive quantitative analysis techniques with the help of descriptive statistics using SPSS and a Likert scale. The results of the study show that employee performance at the Potokullin village office is categorized as fairly good, with the following percentage results: a) quality 47.2%, b) quantity 60.4%, c) task execution 61.8%, d) responsibility 55%, with an average percentage of 56.1%. Meanwhile, community satisfaction at the Potokullin village office is also categorized as fairly good, with the following percentage results: a) service procedures 63.4%, b) service requirements 59.2%, c) service speed 59.6%, d) service fairness 58.6%, with an average percentage of 60.2%. Factors linking employee performance to community satisfaction at the Potokullin village office include: a) ability 55%, b) personality and work interest 55%, c) clarity and acceptance of tasks 56%, d) level of work motivation 57.8%, e) competence 50.2%, f) work facilities 54.8%, g) work culture 55.2%, h) leadership 57.4%, i) work discipline 55%, with an average percentage of 55.15%.